ACTUALIZATION OF NATIONAL ORNAMENT IN BRANDING AND THE FASHION INDUSTRY - Mavlonova Munavvar Iskandar qizi (Bright Mind Publishing, 2026)
In the context of globalization and the intensification of intercultural exchange, the fashion industry has become not only a sector of material production but also a powerful medium for the transmission of cultural identity, symbolic meaning, and national self-representation. Branding, as a strategic communicative system within the fashion industry, increasingly relies on cultural codes to establish emotional connections with consumers and to differentiate products in a saturated global market. This article examines the актуалization (recontextualization and functional renewal) of national ornament within branding practices of the fashion industry, emphasizing its role as a carrier of historical memory, aesthetic philosophy, and socio-cultural values. The research explores theoretical foundations of ornament as a semiotic system, analyzes contemporary branding strategies that integrate national ornamental motifs, and evaluates their effectiveness in reinforcing brand identity and cultural authenticity. Special attention is given to the challenges of preserving semantic integrity while adapting traditional ornamentation to modern design languages and global market requirements. The study employs interdisciplinary methodologies combining cultural studies, design theory, semiotics, and marketing analysis. The results demonstrate that the competent integration of national ornament into fashion branding not only enhances visual recognition and market competitiveness but also contributes to the sustainable development of cultural heritage within creative industries.
Keywords: National ornament; fashion branding; cultural identity; design semiotics; visual communication; fashion industry; heritage-based design; creative economy.